2018
DOI: 10.1039/c8ra08893d
|View full text |Cite
|
Sign up to set email alerts
|

Morphology dependent nonlinear optical and photocatalytic activity of anisotropic plasmonic silver

Abstract: Anisotropic plasmonic silver for nonlinear optical and photo catalytic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Due to the refractive index gradient, the medium acts as a lens‐like optical element, called TL . When a probe beam passes through the spatially varying refractive index (lens), it gets diverged or focused depending upon the coefficient of refractive index with temperature, dndT. The negative value of dndT0.25emshows that the TL formed will be a diverging one resulting in thermal blooming. Measurement of time‐dependent beam intensity is more viable in a mode matched pump–probe collinear arrangement than to measure the spot size directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the refractive index gradient, the medium acts as a lens‐like optical element, called TL . When a probe beam passes through the spatially varying refractive index (lens), it gets diverged or focused depending upon the coefficient of refractive index with temperature, dndT. The negative value of dndT0.25emshows that the TL formed will be a diverging one resulting in thermal blooming. Measurement of time‐dependent beam intensity is more viable in a mode matched pump–probe collinear arrangement than to measure the spot size directly.…”
Section: Resultsmentioning
confidence: 99%
“…The focal length f of the induced TL, when a continuous‐wave laser beam is passed through a sample, at t = 0 is shown below 10.25embold-italicf=Pabsdndtbold-italicπkω2()bold1+bold-italictbold-italiccbold2bold-italict Where P abs is the power absorbed by the sample, k is the thermal conductivity, ω is the beam radius, and t c is the characteristic time for thermal diffusion is given by tc=bold-italicωbold2bold4bold-italicD Where, D is the thermal diffusivity …”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect that determines the optical properties of plasmonic nanoparticles is the surface morphology, as the optical response is strongly influenced by the surface characteristics as well as shape. [49] González et al demonstrated moderately pronounced effect of the surface morphology on the optical spectra for small Ag nanoparticles from 4 to 13 nm in size. [50] The morphological irregularities in the larger particles synthesized by Bastús et al [8] is clear from their TEM images (Figure S2) and it is possible that they might be playing a significant role in shaping the optical spectra.…”
Section: The Deviation Of Theoretical Predictions From Experimental O...mentioning
confidence: 99%
“…Second and third harmonic generation measurements in amorphous ZnO thin films has been performed by rotational Maker fringe technique using Nd:YAG laser at 1064 nm in picosecond range for the verification of the nonlinear optical properties [51]. In addition, it has been found that the restricted motion of excitons and phonons can impact nonlinear functionalities of the nanomaterials depending on their shapes and sizes [52][53][54]. Indeed, many research articles have illustrated diverse methodologies to understand the morphology-dependent optical nonlinearities.…”
Section: Introductionmentioning
confidence: 99%